Evaluating the functional and genomic analysis of pathogenic junctophilin-2 variants and their association with the pathogenesis of cardiomyopathy to understand their molecular impact on cardiac calcium homeostasis and disease phenotypes - Muhammed Ali Siham (Annals of Pediatric Cardiology)
The growing body of evidence suggests that junctophilin-2 (JPH2) variants hold significant potential for diagnostic and therapeutic interventions, particularly within the framework of personalized medicine and genetic screening across diverse populations. Mutations in JPH2 have been associated with a range of clinical phenotypes including early-onset heart failure and cardiomyopathies, a diverse group of diseases affecting heart muscle structure and function that contribute to heart failure and sudden cardiac death. While traditional understanding has centered on sarcomeric gene mutations, recent studies have shifted attention toward calcium-handling genes such as JPH2. This study consolidates insights from original research, preclinical studies, case reports, and editorials to highlight JPH2’s impact on cardiomyopathies and associated disease phenotypes.